2013
DOI: 10.1371/journal.pntd.0002402
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased Expression of MicroRNAs in Schistosoma mansoni

Abstract: Schistosomiasis is an important neglected tropical disease caused by digenean helminth parasites of the genus Schistosoma. Schistosomes are unusual in that they are dioecious and the adult worms live in the blood system. MicroRNAs play crucial roles during gene regulation and are likely to be important in sex differentiation in dioecious species. Here we characterize 112 microRNAs from adult Schistosoma mansoni individuals, including 84 novel microRNA families, and investigate the expression pattern in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 47 publications
6
83
0
Order By: Relevance
“…Each of these sex-biased miRNAs exhibited sex-biased expression in adults, but sex-biased miRNA expression was lower in pre-adults (with 5% and 4% of the total miRNAs being sex biased in larvae and pupae, respectively). Genome-wide sex biases in miRNA expression have also been identified in zebra finches (Luo et al 2012), silkworm (Liu et al 2010), schistosomes (Marco et al 2013), and halibut brain and gonad tissue (Bizuayehu et al 2012). In halibut, patterns of sex-biased expression suggest a role of miRNAs in sexual development.…”
Section: Sex-biased Gene Expression and Sexual Conflictmentioning
confidence: 98%
See 1 more Smart Citation
“…Each of these sex-biased miRNAs exhibited sex-biased expression in adults, but sex-biased miRNA expression was lower in pre-adults (with 5% and 4% of the total miRNAs being sex biased in larvae and pupae, respectively). Genome-wide sex biases in miRNA expression have also been identified in zebra finches (Luo et al 2012), silkworm (Liu et al 2010), schistosomes (Marco et al 2013), and halibut brain and gonad tissue (Bizuayehu et al 2012). In halibut, patterns of sex-biased expression suggest a role of miRNAs in sexual development.…”
Section: Sex-biased Gene Expression and Sexual Conflictmentioning
confidence: 98%
“…These miRNAs target mRNAs with complementary sequences and bind to them to regulate their expression, potentially by tagging the mRNA for destruction, or by preventing their translation (Pasquinelli 2002). Relatively little is known about sex-biased expression of miRNAs, although RNA-sequencing in the zebra finch, Taeniopygia guttata, has found genome-wide sex-biased expression of some miRNAs (Luo et al 2012), and patterns of sex-biased miRNA expression have also been found in halibut (Bizuayehu et al 2012), silkworm (Liu et al 2010), and schistosomes (Marco et al 2013). Taken together with the evidence for sex-biased miRNA expression in D. melanogaster from our unpublished data described below, it seems that further research on the sex-specific functions of miRNAs could shed some light on the mechanisms that control sex-biased gene expression.…”
Section: Sex-biased Gene Regulation and Evolutionmentioning
confidence: 99%
“…Eighteen miRNAs are male-specific and just one (miR-9459) is female-specific (enrichment in one sex > 10, with Fisher's exact test P-value < 0.01). Sex-specific miRNAs have also been reported in mammals and flatworms and may exist in fish and birds (Wienholds et al 2005;Ciaudo et al 2009;Hao et al 2010;Luo et al 2012;Marco et al 2013).…”
Section: Spatiotemporal Regulation Of Nematostella Mirnasmentioning
confidence: 99%
“…Analysis of small RNAs expressed in S. mansoni adult male or female worms identified 10 female enriched and 3 male enriched miRNAs (Marco et al, 2013). While the mir-2/mir-71 cluster is duplicated in schistosomes, the cluster located on chromosome 5 (autosome) shows female-biased expression while that on the sex chromosome does not.…”
Section: Micrornas In Helminthsmentioning
confidence: 99%